Are alternative meanings of an Arabic homograph activated even when it is disambiguated by vowel diacritics?. Issue 2 (3rd July 2019) - Maroun, Maryse; Hanley, J. Richard
ABSTRACT: The diacritical markers that represent most of the vowels in the Arabic orthography are typically omitted from written texts, thereby making many Arabic words phonologically and semantically ambiguous. Such words are known as heterophonic homographs and are associated with different pronunciations and meanings. The three experiments reported in this paper were conducted to investigate how Arabic readers understand diacritised heterophonic homographs. The results suggested that even when diacritics were added to disambiguate a heterophonic homograph, it was still initially processed as if it was ambiguous and its alternative meaning(s) were activated.